Osip Mandelstam’s "Stone". New data: variants of poems and author’s notes - Alexander Mets (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2021)
This article describes a copy of Osip Mandelstam’s Stone with the author’s notes and variants of the poems. It mentions V.I. Ivanov, O.A. Glebova-Sudeikina, the Timofeev family.